The effect of health-promoting leadership of nursing managers on the work withdrawal behaviors and psychological safety of nurses - Darya Esmaeilbeigi; Mahdi Sahraei Beiranvand; Fatemeh Mohammadipour (PLoS ONE, 2025)
Aim Health-promoting leadership is a novel organizational strategy aimed at preventing the occurrence of diseases in the workplace and promoting the health needs of staff. The present study aimed to investigate the effect of health-promoting leadership of nursing managers on the nurses’ withdrawal behaviors and psychological safety. Design Structural equation modelling was used to verify the conceptual model. Methods A total of 346 nurses working in educational hospitals in the western provinces of Iran were included using stratified random sampling by 2023. The research instruments included a checklist of demographic and occupational characteristics, health-promoting leadership, withdrawal behaviors, and psychological safety questionnaires. Pearson’s correlation and structural equation modelling were used to investigate the relationships between the variables. We followed the STROBE Checklist. Results The findings showed a significant negative relationship between health-promoting leadership and withdrawal behaviors and a significant positive relationship with nurses’ psychological safety. There was also a negative and significant relationship between the withdrawal behaviors and psychological safety. Health-promoting leadership can explain 45% and 52% of the variance in psychological safety and withdrawal behaviors, respectively. Conclusions While emphasizing the importance of leadership styles, the findings of this study indicate that nurse leaders should acknowledge the significance of health promotion leadership as a crucial set of behaviors to foster psychological safety and reduce withdrawal behaviors among nurses, thereby enhancing their quality of care and performance. Implications for nursing management The results draw the attention of nursing managers to health-promoting leadership and its relationships, and create an impetus for changing leadership styles and addressing the lack of mutual understanding. Considering this finding, it appears necessary to create clearer prospect for the nursing profession by teaching health-promoting leadership principles to nursing managers and nurses without managerial positions.